O Instituto Universitário de Educação de Cabo Verde e os desafios da universitarização para a formação de professores - Gomes, Janice Raquel Sança (2016)
The Cape Verdean education since independence has undergone several changes in order to increase access to education and provide teachers with specific training. Reforms and educational policies in Cape Verde in turn have demanded increasingly higher teacher qualifications and highlighted their role in improving the quality of education. In this sense, in 2010, the Decree Legislative n.2 / 2010, increased teacher training for basic education in superior level. Therefore, the research sought to understand the implications of universitarization process in the formation of Cape Verdean teachers of basic education (mostly with a single mid-level training), after attending an undergraduate complement course at University Institute Education. As a research methodology was adopted a qualitative approach of the analytical-descriptive and interpretative-critical, based on the analysis of semi-structured interviews with the studentes and the coordinators. Their research shows the emphasis of technical rationality; in teacher training; the discontinuity of educational policies regarding the training of teachers and consequently in education; the notion of competence in the training of teachers related the demands of the labor market and a flexible professional. On the other hand, we found that teacher training is a continuous process, composed of various elements in addition to formal courses; It is not as easy demarcation of functions of initial and continuing education, and the course played a dual purpose as an initial training course, with continued training function. In addition, the University Institute of Education, although it does not represent the full motion universitarization, presents elements that show that this phenomenon is in full development.